Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1530-0277.2011.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intestinal Circadian Genes in Alcohol-Induced Gut Leakiness

Abstract: Background Several studies have indicated that endotoxemia is the required co-factor for alcoholic steatohepatitis (ASH) that is seen in only about 30% of alcoholics. Recent studies have shown that gut leakiness that occurs in a subset of alcoholics is the primary cause of endotoxemia in ASH. The reasons for this differential susceptibility are not known. Since disruption of circadian rhythms occurs in some alcoholics and circadian genes control the expression of several genes that are involved in regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 52 publications
(77 reference statements)
3
51
0
Order By: Relevance
“…The concentration of ethanol used in our study is not cytotoxic as shown previously that ethanol at a concentration of 0.2% v:v (;40 mmol/L), which can be achieved in blood after moderate (2-4 drinks; 1 standard drink, ;14 g of ethanol) consumption (30,31), can disrupt epithelial TJ integrity in a Caco-2 3-dimensional cell culture model without compromising cell viability (3). Our findings are also in agreement with previous observations by others showing that ethanol can disrupt the TJ integrity, resulting in increased paracellular permeability (30,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 66%
“…The concentration of ethanol used in our study is not cytotoxic as shown previously that ethanol at a concentration of 0.2% v:v (;40 mmol/L), which can be achieved in blood after moderate (2-4 drinks; 1 standard drink, ;14 g of ethanol) consumption (30,31), can disrupt epithelial TJ integrity in a Caco-2 3-dimensional cell culture model without compromising cell viability (3). Our findings are also in agreement with previous observations by others showing that ethanol can disrupt the TJ integrity, resulting in increased paracellular permeability (30,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 66%
“…In a different cohort, while disease related symptoms was a key determinant of impaired sleep quality, poor sleep even during remission was associated with an increased risk of symptomatic disease flares at 6 months 10 . Experimentally, interleukin-6 (IL-6), interleukin-1 (IL-1), and tumor necrosis factor (TNF) directly induces fatigue and sleep 2224, 3840 . Intravenous or intra-cerebroventricular injections of recombinant TNF suppresses rapid-eye-movement (REM sleep) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A method of assessing integrity of peripheral circadian homeostasis is the measurement of core circadian genes such as CLOCK and PER genes in circulating blood monocytes or tissue clock genes in intestine or liver. Our recent work showed that alcohol in-creased circadian clock genes, CLOCK and PER2, in intestinal epithelial cells, CaCo-2 cells, and blocking CLOCK or PER2 with small-interfering RNA prevented alcohol-induced hyperpermeability (44). Our subsequent studies in mice have shown that circadian disruption, either environmental or genetic, increases alcohol-induced intestinal permeability and liver injury (43).…”
mentioning
confidence: 99%